Trends and characteristics of global medical informatics conferences from 2007 to 2017: A bibliometric comparison of conference publications from Chinese, American, European and the Global Conferences. (November 2018) - Jia, Yuxi; Wang, Wei; Liang, Jun; Liu, Li; Chen, Zhenying; Zhang, Jiajie; Chen, Ting; Lei, Jianbo
Highlights: The experience of China's considerable investments in HIT has not been compared with relevant research in USA or Europe (EU). The current hotspots and trends in MI development among China, USA and EU were analyzed, from the perspective of conferences. 2285, 1601, 1930, 5431 papers were publicized from the target USA, EU, Global, Chinese MI conferences between 2007 and 2017. The H-index of the USA, EU, Global and Chinese MI conferences proceedings between 2007 and 2017 were 32, 19, 19 and 3. Given the size of the Chinese economy and the substantial investment in MI, the output in terms of conferences remains low. Abstract: Background: As the second-largest economy in the world, China has invested considerable financial and policy support into hospital informatization since health care reform in 2010. However, the results and experience of such investments have not been compared with relevant research and applications in the United States and Europe. Objectives: From the perspective of professional conference proceedings, we comparatively analyzed the current situations, characteristics, hotspots, and trends of medical informatics (MI) development in China, the United States and Europe to help Chinese MI researchers and practitioners summarize their experiences and determine gaps compared to their American and European peers. We also aimed to educate foreign peers about the special contributions of the China MI circle and facilitate multilevel international cooperation. Methods: English conference proceedings of the American Medical Informatics Association (AMIA) Annual Symposium (USA), Medical Informatics Europe (MIE, Europe) and World Conference on Medical Informatics (MEDINFO, Global) from 2007 to 2017 were searched within Scopus and Pubmed. Proceedings of Chinese MI conferences (CMIAAS, CHINC, CHITEC, CPMI) (China) were searched within Chinese databases CQVIP, CNKI and WanFang during the same period. The datasets were preprocessed via a Natural Language Processing (NLP) package on Python and were qualitatively and quantitatively analyzed via bibliometric methods. Results: Overall, 2285, 1601, 1930 and 5431 papers were publicized from the AMIA Symposium (USA), MIE (Europe), MEDINFO (Global) and Chinese MI conferences (China) between 2007 and 2017, respectively, with an H-index of 32, 19, 19 and 3, respectively. The AMIA Symposium, MIE and MEDINFO received submissions from 43, 68 and 80 countries (or regions), respectively, but Chinese MI conferences (CMIAAS, CHINC, CHITEC, CPMI) only received submissions from 3 foreign countries. Author affiliations were quite similar among the AMIA Symposium, MIE and MEDINFO, as 67%, 75% and 70% of authors came from universities/colleges, respectively; 18%, 10% and 11% came from medical institutions, respectively; and 7%, 8% and 10% came from institutes, respectively. In contrast, the majority (54%) of authors in Chinese MI conferences came from medical institutions followed by universities/colleges (17%) and institutes (10%). Of the top 5 authors with the most publications in AMIA Symposium, MIE and MEDINFO, 14/15 of them had medical backgrounds, but only one author from the Chinese MI conferences majored in medicine. Electronic medical records (EMR) were included in the top 10 high-frequency keywords by all four conference groups, but the amount of time that this keyword appeared differed in 2009, 2011, 2012 and 2013, respectively. Conclusions: The MI annual conferences are all different among China, the United States and Europe. China lags in the theoretical and discipline bases but has made considerable investments in the past 10 years. China should fully use its second-mover advantage and application advantages and utilize international experiences and cooperation to make stronger contributions to global MI development.